(untitled) (Journal of the Bangladesh Agricultural University, 2010)
A field experiment was conducted at the Bangladesh Agricultural University (BAU) to find out possible effects of alternate wetting and drying irrigation (AWDI) on the yield, water use and water use efficiency (WUE) of Boro rice. The experimental layout was furnitured using split-plot design (SPD) with two modern varieties (MV) of rice viz. BRRIdhan 28 and BRRIdhan 29, which received four irrigation treatments randomly and was replicated thrice. The treatments ranged from continuous submergence (T1) of the field to a number of delayed irrigations (T2, T3 and T4) denoting application of 5 cm irrigation water when water level in the perforated PVC pipe fell 10, 20 and 30 cm below ground level (G.L.), respectively. The study revealed that treatment T1 attributed by the highest total water use (122.2 cm) and the lowest WUE (58.53 kg/ha/cm) produced the highest grain yield (6.86 t/ha). Treatment T2, on the contrary, gave the second highest yield (6.58 t/ha) and consequently the second highest WUE (69.48 kg/ha/cm) indicating quite a large water saving (15 cm) compared to treatment T1. The yields in treatments T3 (6.27 t/ha) and T4 (5.86 t/ha) were significantly lower at 1% level of significance compared to that of treatment T1. No significant effect was found either for the treatment or for the varieties on the number of effective and total tillers hill-1 nor did they affect 1000 grain weight. Reduced plant height, no. of effective tillers hill-1, grain yield, straw yield, biological yield and harvest index were found with the increasing water stress. Key words: Alternate wetting and drying irrigation; Boro rice; Yield; Water use efficiency DOI: 10.3329/jbau.v6i2.4841 J. Bangladesh Agril. Univ. 6(2): 409-414, 2008